HUBUNGAN STATUS GIZI DAN TINGKAT PENGETAHUAN DENGAN KEJADIAN ANEMIA PADA REMAJA PUTRI HUBUNGAN STATUS GIZI DAN TINGKAT PENGETAHUAN DENGAN KEJADIAN ANEMIA PADA REMAJA PUTRI - Mira Suminar; dyah juliastuti; Tias Nuri Febriyan (Jurnal Kesehatan STIKes IMC Bintaro, 2022)
Introduction anemia in adolescents is a public health problem in Indonesia that needs special attention. The impact of anemia in adolescent girls is fatigue, decreased concentration in learning so that learning achievement is low and can reduce adolescent productivity. Besides, it also lowers the body's resistance so that it is easy to get infections. Research Objectives: To determine the relationship between nutritional status and level of knowledge with the incidence of anemia in adolescent girls at SMA Bina Insani Tangerang. Methods: This research is a type of quantitative research by using a cross sectional study design using stratified random sampling technique. The sample in this study were students of class X and XI SMA Bina Insani Tangerang in March 2022 as many as 45 respondents. This study uses a questionnaire on the level of knowledge of anemia that has been tested for validity and reliability, using the easy touch gchb tool, and anthropometric measurements (BMI). Research Results: Based on the research, the results of the analysis using the Chi-Square test between the nutritional status variables and the incidence of anemia were obtained p = 0.001 (p <0.005), the level of knowledge was p = 0.003, which means that it can be concluded that there is a relationship between nutritional status and the level of knowledge with the incidence of anemia. anemia in adolescent girls at SMA Bina Insani Tangerang. Suggestion: It is expected to increase knowledge related to body mass index and knowledge about anemia in an effort to overcome and minimize the risk of anemia in adolescent girls.